Bijak Peribahasa : An Adventure Game In Learning Malay Proverb - Mokhtar, Siti Nur Shafirah; Othman, Siti Khadijah; Hasnan, Mazliana; Dahlan, Azlin (2020)
Bahasa Melayu is one of the core subjects that students need to pass in Ujian Penilaian Sekolah Rendah (UPSR). From the preliminary study, the findings showed that students find it hard to memorize the Malay proverb and its meaning. Moreover, students only learn Malay proverbs during class sessions and only memorize for exams without understanding the meaning. The purpose of this project is to design and develop game-based learning applications for UPSR students in learning Malay Proverb. The project was implemented as a Game-based Learning Model as a guideline to develop the application, which involves nine factors including game goal, game fantasy, challenge, game mechanism, sensation, interaction, freedom, game value and mystery. The Game Development Life Cycle Model (GDLC) was implemented as a methodology in this project. Findings of evaluation shows that the game receives 96% level of agreeability as response by the users of the game. Future work for this game is to develop this game on mobile platform, improve by adding multi-player, provide high score for players and enhance the contents of the game.